Analysis of Preventive Behavior of Leucorrhea in Hormonal Injection Contraceptive Users at Rappokalling Health Center, Makassar City - Linda Hardianti Saputri; Samsu Alam; Nurul Husnah (Pancasakti Journal Of Public Health Science And Research, 2025)
Vaginal discharge is a common reproductive health issue that requires prompt and appropriate management to prevent complications such as pruritus, genital edema, dysuria, and lower abdominal or back pain. This study aimed to examine factors associated with vaginal discharge prevention behavior among injectable hormonal contraceptive users. A cross-sectional analytical design was employed in the Rappokalling Community Health Center area, Makassar, from September to December 2023. A total of 63 respondents met the inclusion criteria and participated in the study. Data were collected using a structured questionnaire measuring four key variables: self-motivation, perceived benefits, interpersonal influence, and commitment to action. Statistical analysis was conducted using SPSS software with chi-square tests to identify associations between these variables and preventive behavior. Findings revealed significant associations between prevention behavior and both self-motivation (p = 0.002) and perceived benefits (p = 0.005). While interpersonal influence (p = 0.078) and commitment to action (p = 0.309) were not statistically significant, their potential behavioral influence remained evident. Women with higher self-motivation and perceived benefits tended to adopt better preventive practices. Additionally, those influenced by supportive interpersonal environments demonstrated stronger prevention behaviors, whereas respondents with lower commitment to action showed weaker engagement in preventive measures. These findings highlight the importance of strengthening intrinsic motivation and perceived benefit to enhance vaginal discharge prevention among injectable contraceptive users.